The role of price and cost competitiveness for intra- and extra-euro area trade of euro area countries - Elena Bobeica; Styliani Christodoulopoulou; Olegs Tkačevs (European Central Bank (ECB), 2016)
This paper studies the importance of price and cost competitiveness for intra- and extra-euro area trade flows of euro area countries. A standard error correction framework shows that price competitiveness is a relatively more important driver of trade flows outside the euro area as compared to those within the monetary union, especially for exports, that tend to be more sensitive to relative prices than imports. We consider various measures of competitiveness and conclude that it is difficult to single out one that outperforms the others; based on an encompassing test, measures based on labour costs appear to contain relatively more information for trade flows, particularly for exports outside the euro area. The key policy implication is that to adjust competitiveness disequilibria within the monetary union, measures besides those aimed at price and cost adjustments should be pursued in the deficit countries, such as structural policies fostering non-price competitiveness.
Keywords: F14; F15; F41; 330; error correction model; intra- and extra-euro area trade; price and cost competitiveness